Redes inalámbricas y técnicas de minería Web aplicadas a un modelo de telemedicina - Cifuentes García, Carlos Andrés (2011)
This paper presents the integration of two technology tendencies: telemedicine and web mining with the aim of propose a model of real-time diagnosis, along with added services for consultation and monitoring to assist medical staff to use new tools ICT for disease diagnosis. It has defined four stages: (A) Design of hardware, including communications and sensor integration of the patient. (B) Implementation of the Zigbee network for monitoring biomedical sensors. (C) Classification of information Web on medical domain, (D) Development of an algorithm for extraction and information integration. The results are presented as biomedical signal transmission to Internet server in real time, and extracted classified information internet medical domain, in order to generate diagnoses and treatment based on patient monitoring.